The Influences of Solvency, Cash Flow Ratio and Profitabiliy toward Going Concern Opinion - Ery Yanto; Pandu Cakranegara (President University Press, 2021)
In providing an audit opinion, some assumptions must be met, one of which is that it will continue. In terms of corporate sustainability accounting, this is called a going concern. To evaluate whether the company has a going concern, an auditor can look at several indicators. These indicators include solvency, cash flow, and profitability. This study attempts to investigate the effect of these three variables towards audit going concern. Multiple linear regression statistical methods are used to link them with the going concern level. Based on the research results on 56 companies listed on the Indonesia Stock Exchange from 2017 to 2019, it can be concluded that solvency, cash flow, and profitability significantly affect the company.